Natural rate chimera and bond pricing reality - Claus Brand; Gavin Goy; Wolfgang Lemke (European Central Bank (ECB), 2021)
We build a novel macro-finance model that combines a semi-structural macroeconomic module with arbitrage-free yield-curve dynamics. We estimate it for the United States and the euro area using a Bayesian approach and jointly infer the real equilibrium interest rate (r*), trend inflation (Û*), and term premia. Similar to Bauer and Rudebusch (2020, AER), Û* and r* constitute a time-varying trend for the nominal short-term rate in our model, rendering estimated term premia more stable than standard yield curve models operating with time-invariant means. In line with the literature, our r* estimates display a distinct decline over the last four decades.
Keywords: C11; C32; E43; G12; E44; E52; 330; Natural rate of interest; r*; equilibrium real rate; arbitrage-free Nelson-Siegel termstructure model; term premia; unobserved components; Bayesian estimation